Watersheds of Florida: Understanding a Watershed Approach to Water Management - Rao Mylavarapu; Kelley Hines; Thomas Obreza; Greg Means (EDIS)
Water is of primary importance to all life on earth. Freshwater is a finite resource, and managing freshwater requires an understanding of watersheds and a watershed approach. Both quantity and quality of water are important for balanced beneficial and efficient agricultural, industrial, rural, and urban uses. This 7-page fact sheet provides information on watersheds and introduces the watershed approach and management concept as practiced in the U.S., with a focus on Florida watersheds in particular. This document also provides information on the basins, basin groups, and hydrologic units of Florida used by the Florida Department of Environmental Protection (FDEP) to implement watershed assessment, monitoring, and restoration programs. Written by Rao Mylavarapu, Kelley Hines, Thomas Obreza, and Greg Means, and published by the UF Department of Soil and Water Science, July 2012.